Pengaruh Pasta Ekstrak Daun Tembakau terhadap Kekuatan Transversa Gigi Tiruan Resin Akrilik Heat Cured - Lestari, Diah Ayu; Soesetijo, FX Ady; Parnaadji, Rahardyan (Denta Journal Kedokteran Gigi, 2026)
Background: Removable dentures are prosthetic devices used to replace missing teeth. Acrylic resin is the most commonly used material for denture base fabrication. Plaque accumulation on improperly cleaned denture bases can lead to denture-associated stomatitis. Tobacco leaves have potential as a denture cleaning paste due to their antibacterial and antifungal properties. However, their phenol content may degrade polymer bonds and reduce the transverse strength of heat-cured acrylic resins. Objective: This study aims to investigate the effect of using 25% and 50% tobacco leaf (Nicotiana tabacum L.) extract paste as a denture cleaning agent on the transverse strength of heat-cured acrylic resin. Method: This study used an experimental laboratory design with a post-test-only control group. Thirty rectangular block-shaped samples (60x12x3 mm) were divided into one control group (K) and two treatment groups (n=10), which were brushed with 25% (T1) and 50% tobacco leaf extract paste (T2), respectively, for 28.2 minutes. Transverse strength was tested using a universal testing machine with the three-point bending test method. Results: The transverse strengths of groups K (126.926 MPa), T1 (103.136 MPa), and T2 (83.001 MPa) were determined. The parametric test results indicated significant differences between groups K and T2 (p=0.001) and between T1 and T2 (p<0.001). However, no significant difference was observed between groups K and T1 (p=0.052). Conclusion: This study found a decrease in the transverse strength of heat-cured acrylic resin after brushing with tobacco leaf extract paste.